The Matthew Effect in Economics Reconsidered - Daniel Birkmaier; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2014)
We apply the test of Ijiri and Simon (1974) to a large data set of authors in economics. This test has been used by Tol (2009, 2013a) to identify a (within-author) Matthew effect for authors based on citations. We show that the test is quite sensitive to its underlying assumptions and identifies too often a potential Matthew effect. We propose an alternative test based on the pure form of Gibrat's law. It states that stochastic proportionate citation growth, i.e. independent of its size, leads to a lognormal distribution. By using a one-sided Kolmogorov-Smirnov test we test for deviations from the lognormal distribution which we interpret as an indication of the Matthew effect. Using our large data set we also explore potential empirical characteristics of economists with a Matthew effect.
Keywords: A12; A14; 330; Matthew Effect; Gibrat's Law; Kolmogorov-Smirnov